Chromatography : a century of discovery 1900-2000 : the bridge to the sciences/technology - Gehrke, Charles W.; Wixom, Robert L.; Bayer, Ernst (Journal of chromatography library, 2001)
Chromatography - A Century of Discovery 1900-2000 represents the combined thinking and contributions of many chromatographers. It includes several in-depth feature chapters covering the Beginnings of Chromatography, which highlights M.S. Tswett, the inventor of chromatography, and several other early pioneers. Included are the contributions of several Nobel Laureates, and 125 Chromatography Award Winners and contributors, an extensive bibliography of publications on the History of the Evolution of Chromatography; a presentation of Major International Symposia supporting chromatography and as a bridge to selected sciences. Special chapters are written by well-known Chromatographers on Support and Stationary Phases, and Separations followed by a chapter on Milestones and Paradigm Shifts in Science. New discoveries in the life sciences and medicine, agriculture, the environment and separations technology in the 21st century will rely immeasurably on the 20th century research tools in chromatography and those yet to be developed.